Pengaruh Waktu Maserasi dan Konsentrasi Pelarut Etanol Terhadap Rendemen dan Aktivitas antioksidan pada Bayam Merah (Amaranthus tricolor L) - Hilma Maulia Khoirunnisa; Ahmad Muhammad Fuadi (Jurnal Ilmiah Teknik Kimia, 2023)
As technology advances, it results in environmental pollutants, UV rays, and ionizing radiation which cause various diseases due to tissue damage due to the presence of free radicals, where free radicals attack healthy body cells. One of the compounds that can inhibit free radicals is antioxidants. which can provide endogenous protection and exogenous oxidative stress by scavenging free radicals. The body's defense system that can be used to fight free radicals is food. One of the foods that contain antioxidants is red spinach (Amaranthus tricolor L.). The purpose of this study was to determine the effect of maceration time and optimum concentration of etanol solvent on yield and antioxidant activity. The extraction used was the maceration method with variations in maceration time of 24, 48.72, and 96 hours and solvent concentrations of 55%, 65%, 75%, 85%, and 96%. Then it was filtered using filter paper and evaporated using a vacuum rotary evaporator to obtain a viscous extract, after which the yield of the extract was calculated, tested for phytochemical antioxidant content, and tested for antioxidant activity using the DPPH method. The results showed that maceration time and etanol solvent concentration affected the yield and antioxidant activity of red spinach etanol extract. The best treatment for optimum results was the variation of maceration time for 96 hours using 96% etanol concentration, which resulted in a yield of 19,40 grams and an antioxidant activity of 22,70 mg/L.